Analysis of the Application of the M-Apos Learning Model to the Improvement of Prospective Teachers’ Computational Thinking Skills - Sari, Dwi Maulida; Suhendra, Suhendra; Nurlaelah, Elah; Jupri, Al; Wicaksono, Agung; Warli, Dwi; Raisatunnisa, Raisatunnisa; Mansyur, Muhamad Zulfikar (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to analyze the effectiveness of the M-APOS learning model (a modification of Action, Process, Object, and Schema) in improving the computational thinking skills of prospective mathematics teachers. The study employed a mixed-methods approach with an explanatory sequential design that combines quantitative and qualitative data. The research subjects consisted of 44 third-semester students divided into an experimental group (n = 22) and a control group (n = 22). The research instruments included an essay-based computational thinking test, learning activity observation sheets, and interview guidelines. Quantitative data were analyzed using a t-test and Cohen’s d effect size calculation, while qualitative data were analyzed thematically to strengthen the quantitative findings. The results indicate that the M-APOS model significantly improves students’ computational thinking skills, as shown by a Cohen’s d value of 1.57, which represents a very large effect. In addition, observation results show a consistent increase in students’ learning activities, particularly in the indicators of decomposition, pattern recognition, abstraction, and algorithmic thinking. High levels of learning activity support concept internalization through the Action–Process–Object–Schema stages. These findings confirm that the M-APOS model has a substantial impact on students’ computational thinking skills.